Propofol's Effectiveness in Preventing Nausea and Vomiting Following ENT Procedures Performed Under General Anesthesia - Ambareen Sifatullah, Abdullah Babar, Imran Ul Haq, Javed Khan, Navishta Sahar Arif, Abdul Waheed, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Evaluation of Propofol's effectiveness in preventing post-surgery nausea and vomiting after ENT operations performed under general anesthesia Study design: Observational study Sampling method: lottery system Study Place: Peshawar Methods: 70 patients between age 18-65, having elective ENT surgery under conventional general anesthesia were included in this observational. After the surgical procedure, the patients were given either 10 mg/kg of dexamethasone, or 0.5 mg/kg of propofol intravenously. For 24 hours after surgery, the patients were monitored for any instances of nausea and vomiting. Results: No significant variation in Mean ± S.D of age, gender, BMI, ASA categorization and type of surgery was observed in both dexamethasone and propofol group. A significant variation in surgery duration (p=0.031) and anesthesia time (0.001) was observed in both the groups. PONV was more common in the propofol group (70%) than in the dexamethasone group (40%), particularly in the first six hours after surgery. Practical implication: this study will help to determine the whether propofol is a better choice for preventing post-operative nausea and vomiting. Conclusion: Propofol was less efficient than dexamethasone in preventing PONV, necessitating less rescue antiemetic use. Keywords: ENT, Propofol, nausea, vomiting, post-surgery complication, dexamethasone, effectiveness